Overseas Capital Streams and Economic Growth Nexus: Pragmatic Insights from Nepal - Dahal, Arjun (Adhyayan Journal, 2024)
The objective of the present research is to ascertain the impact of foreign capital inflows, including grants, loans, remittances, and income from tourism, on the economic growth of Nepal. This study utilizes secondary data acquired from several Nepalese economic surveys and World Bank reports. The data consists of 35 data points spanning from the fiscal years 1987/88 to 2021/22. The link between foreign capital inflows and GDP growth in Nepal is examined using fundamental statistical approaches like quantile regression, trace and Max-Eigen cointegration tests, and descriptive statistics. The results show that Nepal's grants, debt, foreign remittances, tourism earnings, and GDP growth co-integrate over the long term. Notably, 80.5 percent of Nepal's GDP growth fluctuation is accredited to foreign grants, loans, remittances, and tourism income. While foreign loans and grants are not statistically significant in and of themselves to measure GDP growth, foreign remittances and tourism income are. For every percentage increase in the median value of remittance and tourism income, the GDP grows by 0.251 and 0.816 percent, respectively. More revenue from tourism than from remittances goes towards Nepal's economic growth. Legislators can, therefore, enact suitable measures to encourage the expansion of the tourism industry